Relationship between teachers’ self-efficacy and age, gender, and marital status among teachers at rural high schools - Dieketseng Mbongo (International Journal of Studies in Inclusive Education)
This study determines the relationship between teachers’ self-efficacy and age, gender, and marital status among teachers at rural high schools in the free state. To measure the effect of demographic variables in efficacy Influence, decision making, efficacy to influence school resources instructional self-efficacy, disciplinary self-efficacy, efficacy to enlist parental Involvement, and efficacy to enlist Community Involvement. This study used the quantitative method and the Bandura Teacher Self-efficacy questionnaire to establish the correlation between variables. Participants were randomly selected from the Thabo-Mofutsanyana district of Free State rural high schools. A descriptive research design was used to interpret the findings, and it was concluded that there was no significant relationship between teacher self-efficacy and gender, marital status, age, and educational level. This means that teachers’ self-efficacy could not depend on demographic variables.